The PENDAYAGUNAAN ZAKAT PRODUKTIF UNTUK PENGUATAN UMKM (STUDI DI LAZISMU DAN BAZNAS KAB BIMA - Rafi, Rafiuddin (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research examines the utilization of productive zakat in increasing the income of business groups, especially in the Micro, Small and Medium Enterprises groups (UMKM) which are located and funded by the National Zakat Amil Agency (Baznas) and the Muhammadiyah Regency Amil Zakat Infaq and Sadaqah Institute(LAZISMU) To deepen the study, the researcher first took pictures of the model and impact of utilizing productive zakat on UMKM, secondly the researchers took pictures of the obstacles and solutions faced by Baznas and Lazismu in utilizing productive zakat. As data analysis material in this research, researchers used empowerment theory and needs theory. These two theories are combined in the study to explore the model and the impacts and obstacles faced by Baznas and Lazismu. Specifically, Gozali's theory of needs is used as an approach in Islamic Economics. Apart from theory, researchers also slice the data into rules or laws related to zakat management in Indonesia. Meanwhile, the method used is descriptive qualitative, data collection uses semi-structured interview techniques and document study. The research results show that the productive zakat utilization model in Baznas and Lazismu is structured and well planned, while the impact on mustahik or UMKM still needs to be evaluated in depth. Apart from that, the obstacles faced are the management of zakat/mustahik data which is not yet optimal, a shortage of personnel and a lack of understanding about zakat for personnel as well as a lack of zakat income/funds. Key words: Zakat, productive, needs, empowerment, UMKM, utilization